Rule Of Law Mahkamah Syariah Aceh - Seri Mughni Sulubara; Murthada Murthada (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Rule of law is a circus that aims to enforce the law in accordance with existing laws and regulations. The function of the Rule of Law is essentially a formal guarantee of a "sense of justice" for the Indonesian people and also "social justice" so that it was regulated in the preamble of the 1945 Constitution. Map and instructive for state administration. This is so that the law can protect all citizens without any intervention from any party by enforcing and placing the law in the highest position. In this case, any new person can be subject to legal sanctions when the person concerned commits a violation. According to Soerjono Soekanto, the main problem in the Rule of Law lies in its own law (applicable laws and regulations), law enforcers, namely parties who oversee the application of law, facilities or facilities that support the application of law, the society in which the law is enforced and the legal culture in its society. These factors are closely related to the essence of law enforcement. In this article, the author tries to elaborate the Rule of Law of the Aceh Syar’iyah Court